Characteristics Of Factors Influencing The Use Of Injective Contraceptives In World-Age Women In The Amban Health Center, Manokwari, West Papua - Ivonne Junita Fabanjo (Jurnal Kebidanan Sorong, 2021)
ABSTRACT Background: Hormonal contraceptives are the type that is more widely used because of how it works, it is effective, practical, the price is relatively cheap and practical. However, long-term use of injectable contraceptives can cause changes in serum lipids, cause vaginal dryness, decrease libido, emotional disturbances, headaches, acne and can reduce bone density. Research Objectives: To describe what factors influence mothers in choosing injectable contraception. Methods: This type of research is a descriptive study with a cross sectional approach that provides an overview of the factors that influence mothers in choosing injectable contraception. The population in this study were all users of injectable contraceptives at the Amban Health Center in January - April 2020 using the Sampling Technique. Data analysis using the Proportion formula. Results: Age factor < 35 years was 30 (93.75%), experience with past contraceptives was 22 (68.75%), health status without a medical history was 19 (59.38%), side effects experienced side effects amounted to 28 (87.5%). Conclusion: The dominant factor influencing mothers to use injectable family planning is the age factor Keywords: Injectable Contraception, Women, Childbearing Age